Extrapulmonary lymphangioleiomyomatosis mimicking lymphoma metastatic to uterus. Issue 5 (10th December 2014) - Vatansever, Dogan; Sozen, Hamdullah; Iyibozkurt, A. Cem; Comba, Cihan; Yavuz, Ekrem; Topuz, Samet
Abstract Lymphangioleiomyomatosis is a very rare disease that primarily affects the lungs. The atypical smooth muscle cells in these tumors stain both with smooth muscle markers and melanocytic markers characteristically like their counterparts in other members of the PEComa family. Extrapulmonary lymphangioleiomyomatosis, especially without pulmonary involvement, is extremely rare. The clinical importance of lymphangioleiomyomatosis lies in the fact that it may mimic other malignant diseases, such as lymphoma or sarcoma. Here, we report a case of extrapulmonary lymphangioleiomyomatosis without involvement of the lungs, in a patient pre‐diagnosed as having lymphoma metastasized to the uterus or uterine sarcoma.